2009
DOI: 10.3141/2100-08
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Modeling of Perceived Collision Risks in Port Fairways

Abstract: Navigational collisions are one of the major safety concerns in many seaports. Despite the extent of recent works done on port navigational safety research, little is known about harbor pilot's perception of collision risks in port fairways. This paper uses a hierarchical ordered probit model to investigate associations between perceived risks and the geometric and traffic characteristics of fairways and the pilot attributes. Perceived risk data, collected through a risk perception survey conducted among the S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
20
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 21 publications
4
20
0
1
Order By: Relevance
“…This result is expected because pilots do not need to worry about under keel clearance, squat effects, or monitoring an echo-sounder while navigating in deeper waters, which may allow taking risk mitigating actions at an early stage. Debnath and Chin (2009a) have also reported that perceived risk decreases if water depth is higher.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This result is expected because pilots do not need to worry about under keel clearance, squat effects, or monitoring an echo-sounder while navigating in deeper waters, which may allow taking risk mitigating actions at an early stage. Debnath and Chin (2009a) have also reported that perceived risk decreases if water depth is higher.…”
Section: Resultsmentioning
confidence: 99%
“…Effectiveness of navigational lights can also be reduced at night due to bright background lights on shore and from nearby islands (Akten, 2004;Liu, Liang et al, 2006). A number of studies (Chin and Debnath, 2009;Debnath and Chin, 2009a;Debnath and Chin, 2009b) have also reported that pilots perceive higher collision risk at night.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the evidence that can facilitate investigation, the Automatic Information System (AIS) data recorded during the context of the collision are highly informative and have been widely used in previous studies (e.g., Debnath and Chin, 2009;BlokusRoszkowska et al, 2012;Marcjan and Gucma, 2012;Hansen et al, 2013;Wang et al, 2013;Mazaheri et al, 2014).…”
mentioning
confidence: 99%